MOF Nanosheet Reconstructed Two‐Dimensional Bionic Nanochannel for Protonic Field‐Effect Transistors - Wu, Guo‐Dong; Zhou, Hai‐Lun; Fu, Zhi‐Hua; Li, Wen‐Hua; Xiu, Jing‐Wei; Yao, Ming‐Shui; Li, Qiao‐hong; Xu, Gang (Angewandte Chemie International Edition, 2021)
The construction of hydrophobic nanochannel with hydrophilic sites for bionic devices to proximally mimick real bio‐system is still challenging. Taking the advantages of MOF chemistry, a highly oriented CuTCPP thin film has been successfully reconstructed with ultra‐thin nanosheets to produce abundant two‐dimensional interstitial hydrophobic nanochannels with hydrophilic sites. Different from the classical active‐layer material with proton transport in bulk, CuTCPP thin film represents a new type of active‐layer with proton transport in nanochannel for bionic proton field‐effect transistor (H+‐FETs). The resultant device can reversibly modulate the proton transport by varying the voltage on its gate electrode. Meanwhile, it shows the highest proton mobility of ≈9.5×10−3 cm2 V−1 s−1 and highest on‐off ratio of 4.1 among all of the reported H+‐FETs. Our result demonstrates a powerful material design strategy for proximally mimicking the structure and properties of bio‐systems and constructing bionic electrical devices. A MOF thin film‐based bionic proton field‐effect transistor (H+‐FET) has been fabricated for the first time. It displays the highest proton mobility and highest on–off ratio among all reported H+‐FETs.